OPTIMALISASI HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE - Juwari Juwari; Dwi Susil;owati; Hesti Rahayu (Jurnal GeoEkonomi, 2024)
The purpose of this study is to see the optimization of stock prices based on the company's financial performance, seen from the level of liquidity with measuring instruments used current ratio, solvency with measuring instruments used debt ro equity ratio, profitability with measuring instruments used return on assets, and market value with measuring instruments used partial earnings per share. The total population in this study is thirty companies, and a sample of eighteen food and beverage subsector companies listed on the Indonesia Stock Exchange taken through criteria determined by the author. The analysis method used is multiple linear regression. The results of the t test are that the Current Ratio has a negative relationship direction and has a significant effect on the Stock Price, the Debt to Equity Ratio has a negative relationship direction and has an insignificant effect on the Stock Price, Return on Assets and Earnings per Share has a positive relationship direction and has a significant effect on the Stock Price in the food and beverage subsector companies.